Suppression of Dendritic Cell Maturation by Kefir Peptides Alleviates Collagen-Induced Arthritis in Mice - Chen, Chien-Fu; Li, Hsin-Pei; Chao, Ya-Hsuan; Tu, Min-Yu; Yen, Chih-Ching; Lan, Ying-Wei; Yang, Shang-Hsun; Chong, Kowit-Yu; Lin, Chi‐Chien; Chen, Chuan-Mu (Frontiers in Pharmacology, 2021)
Arthritis is a disorder that is characterized by joint inflammation and other symptoms. Rheumatoid arthritis (RA), an autoimmune disease, is one of the most common arthritis in worldwide. Inflammation of the synovium is the main factor that triggers bone erosion in the joints in RA, but the pathogenesis of RA is not clearly understood. Kefir grain-fermented products have been demonstrated to enhance immune function and exhibit immune-modulating bioactivities. This study aims to explore the role of kefir peptides (KPs) on the regulation of dendritic cell, which are found in RA synovial fluid, and the protection effects of KPs on mice with collagen-induced arthritis (CIA). Immature mouse bone marrow-derived dendritic cells (BMDCs) were treated with KPs (2.2 and 4.4 mg/mL) and then exposed to lipopolysaccharide (LPS) to study the immune regulation function of KPs in dendritic cells. Mice with CIA (n=5 per group) were orally administrated KPs (3.75 and 7.5 mg/day/kg) for 21 days and therapeutic effect of KPs on mice with arthritis were assessed. In this study, we found that KPs could inhibit surface molecule expression, reduce inflammatory cytokine release, and repress NF-κB and MAPK signaling in LPS-stimulated mouse BMDCs. In addition, a high dose of KPs (7.5 mg/kg) significantly alleviated arthritis symptoms, decreased inflammatory cytokine expression, suppressed splenic DC maturation and decrease the percentage of Th1 and Th17 in the spleens on mice with CIA. Our findings demonstrated that KPs ameliorate CIA in mice through the mechanism of suppressing DC maturation and inflammatory cytokine releases.